An Overview of Current Projects of Polish Cognitive Ethnolinguistics in Cooperation with Lithuanian Colleagues - Rudenka, Alena (Verbum, 2025)
The overview of current projects of Polish cognitive ethnolinguistics in cooperation with Lithuanian colleagues was presented at “The 9th International Scientific Conference on Linguistic, Educational, and Intercultural Research”, which took place at Vilnius University on 7th -8th November 2024. It reviews the most significant projects of Polish cognitive ethnolinguistics carried out in Lublin, primarily at Maria Curie-Skłodowska University (UMCS). The Lublin Ethnolinguistic School has been developing since the 1980s. Since the beginning of the 21st century, it has closely cooperated with the Institute of Slavic Studies of the Polish Academy of Sciences. The review describes the main works of the Institute of Slavic Studies, the UMCS in Lublin, and other Polish research teams, that were carried out in the mainstream of cognitive ethnolinguistics. Some ideas of the Lublin Ethnolinguistic School are being realized in cooperation with colleagues from Lithuania: Vilnius University, and the Lithuanian Academy of Sciences. The Polish and Lithuanian researchers implement some projects as joint ventures– they are also presented in the overview.